PEMEROLEHAN KOSAKATA BAHASA PERTAMA ANAK KEDUA USIA 16 BULAN - Azis Azis (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
This study aimed to describe the first language vocabulary acquisition (L1) of a second child 16 months of age. The method used in this study is a qualitative method. Data were obtained through direct observation and recording techniques that is processed by reference to the Mukalel theory. Data were analyzed through the steps of identifying, classifying, and describing. Indonesian vocabulary acquisition L1of second child is still at the stage of an incomplete pronunciation of the word. Under the excited conditions, the children can pronounce syllables. While in unhappy condition, no syllables or words that can be spoken, children can only shake the head.